Seasonal variation in physical characteristics of native buck ( Capra hircus) semen in Andhra Pradesh - SRINIVAS, M; NAIDU, K VENUGOPAL; CHETTY, A VENKATAMUNI (The Indian Journal of Animal Reproduction, 2023)
Five native buks aged between 2 to 2a years and weighing about 24.25±2.5 kgs were used to study the seasonal variation in physical attributes of semen. Semen samples were collected twice in a week during winter and summer seasons. The mean values for different semen characteristics were as follows, volume 0. 70±0.10 and 0.60±0.02, mass motility 4.46±0.06 and 4.34±0.08, individual motility(%) 81 .78±0.53 and 78.06±0.68, spenn concentration (x I 09/ml) 2.45±0.31 and 2.35±0.02, live sperm count(%) 87.05±0.62 and 81.11±0.51, abnormal spenn (%) 8.98±0.23 and 9.28±0.20 and intactacrosomes(o/o) 72.68±0.97 and 77.76±0.76 in winter and summer seasons respectively. Seasons had significant effect on semen volume, individual motility, spenn concentration, live spenn count, abnonnal sperms and intact acrosomes acrosomes where as mass motility did not significantly differ between the seasons.